Bioconversion of Fruit Wastes of Papaya, Watermelon, and Banana into Single Cell Protein Production - Thiviya, P.; Kapilan, R.; Madhujith, T. (Tropical Agricultural Research, 2021)
A large quantity of fruit waste is generated in the country which goes into waste creating a number of environmental issues. This fruit waste can effectively be utilized as a substrate to produce single cell proteins. The objective of the present study was to produce single cell proteins from locally available papaya (Carica papaya), watermelon (Citrullus lanatus) and banana fruit (Musa spp.) peel using natural palmyrah (Borassus flabellifer) toddy yeast under liquid state fermentation system. Physiochemical properties: Total Soluble Solids (TSS), reducing sugar, pH, moisture, protein, fat and ash contents of peel samples were determined. Each extract was separately filtered and diluted to 10% with distilled water and subsequently autoclaved. The sterilized peel extracts were inoculated with 5 mL natural palmyrah toddy in triplicate and allowed for fermentation in a shaking incubator at 100 rpm for 48 h. The sediment was collected by centrifugation, oven dried and then the dry weight and protein content were determined. Papaya peel extract generated significantly (p<0.05) higher amount of protein (52.4 ± 0.4%) followed by watermelon (45.2 ± 0.7%) and banana (30.4 ± 0.6%). The fermentation conditions were optimized for SCP production using papaya peel. Protein content observed at 10% substrate concentration, pH 5.0, at 25 ᵒC and 24 h of fermentation were 55.6 ± 0.4%, 53.2 ± 0.7%, 54.5 ± 3.6% and 59.1 ± 0.8%, respectively. Based on the results obtained, papaya peel extract is found to be the best substrate for the SCP production. Natural and locally available papaya peel waste could be a good source for the production of protein-rich cell biomass using liquid state fermentation system by natural toddy yeast of palmyrah.
Keywords: Banana peel; Liquid state fermentation; Papaya peel; Single cell protein; Watermelon peel